(untitled) (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2021)
The article is devoted to the problem of ensuring the ecological safety of the operation of rocket and space complexes. Within the framework of the concept of the controlled descent of the spent first stages of the launch vehicle, a fundamentally new approach to the problem of ensuring the environmental safety of land fall areas is proposed, which ensures fire and explosion safety and a decrease in the size of the fall areas, and the extraction of unused fuel residues in the tanks and pipings of the worked-off stage for performing maneuvers to descend into a given region. The presented original concept consists in a combined method of reducing the anthropogenic impact of the detachable parts of launch vehicles by installing an additional system that provides a controlled descent of the worked-off stages to a given aiming point, and optimizing the fall areas based on the criteria of resistance to the technogenic impact of space rocket launches through the development of information and analytical system. A methodology has been developed for the selection of these sites, based on the creation of an information and analytical system for the area of ​​the fall, which will become an element of the existing system of environmental monitoring of the Baikonur cosmodrome.